Lentiviral vectors transduce lung stem cells without disrupting plasticity - Ashley L. Cooney; Andrew L. Thurman; Paul B. McCray, Jr; Alejandro A. Pezzulo; Patrick L. Sinn (Elsevier, 2021)
Life-long expression of a gene therapy agent likely requires targeting stem cells. Here we ask the question: does viral vector transduction or ectopic expression of a therapeutic transgene preclude airway stem cell function? We used a lentiviral vector containing a GFP or cystic fibrosis transmembrane conductance regulator (CFTR) transgene to transduce primary airway basal cells from human cystic fibrosis (CF) or non-CF lung donors and monitored expression and function after differentiation. Ussing chamber measurements confirmed CFTR-dependent chloride channel activity in CF donor cells. Immunostaining, quantitative real-time PCR, and single-cell sequencing analysis of cell-type markers indicated that vector transduction or CFTR expression does not alter the formation of pseudostratified, fully differentiated epithelial cell cultures or cell type distribution. These results have important implications for use of gene addition or gene editing strategies as life-long curative approaches for lung genetic diseases.